2018
DOI: 10.1159/000494485
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-31 in Diabetic Nephropathy and its Relationship with Inflammation

Abstract: Background/Aims: There is a lack of reliable biological markers for the early diagnosis of diabetic nephropathy (DN) during type 2 diabetes. In this pilot study we aim to assess whether miR-31 levels are modulated by the presence of DN and whether the expression of this miRNA is related to leukocyte-endothelial interactions and inflammation. Methods: Thirty-one T2D patients were enrolled in this pilot study; 18 with no diabetic complications and 13 with diabetic nephropathy. 24 non-diabetic subjects and 13 T2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 31 publications
0
33
0
1
Order By: Relevance
“…Increasing evidences have demonstrated that miRNAs play a key role in the pathogenesis of DN [29,30]. For example, Wang et al [31] found that miR-424 was down-regulated in renal tissues of DN rats and up-regulation of miR-424 obviously improved the symptoms in DN rat models by targeting Rictor.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidences have demonstrated that miRNAs play a key role in the pathogenesis of DN [29,30]. For example, Wang et al [31] found that miR-424 was down-regulated in renal tissues of DN rats and up-regulation of miR-424 obviously improved the symptoms in DN rat models by targeting Rictor.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs generally exhibit regulatory functions on gene expression through acting as microRNA sponge . miR‐31 are reported to present pro‐inflammatory or anti‐inflammatory activities under different condition . Besides, earlier literature reported that miR‐31 presented anti‐inflammatory activity on lung cystic fibrosis and its expression was reduced in lung cystic fibrosis airways .…”
Section: Discussionmentioning
confidence: 99%
“…However, this miR was not among the top 10 miRs regulated in human renal cells or urines from patients. This indicated that a species‐specific miR‐analysis seems to be important as there might be differences in miR‐expression in humans and rats …”
Section: Discussionmentioning
confidence: 99%